GENERAL RECOMMENDATION 33 OF THE CEDAW COMMITTEE AS A STANDARD FOR ACCESS TO JUSTICE FOR WOMEN AND GIRLS (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
The study of the problem of equality and non-discrimination against women is relatively recent and corresponds to the development of human rights in general and the greater visibility of violence and discrimination against women in recent decades. Although the issue of obstacles and barriers faced by women to access justice has been widely studied in our country, serious inequalities and discrimination still exist for the exercise of rights. It is for this reason that in this article we intend to make a brief comment on Recommendation 33 of the CEDAW Committee as we believe it can contribute to a greater awareness of the problem of access to justice with a gender perspective in all areas of law.
Keywords: general recomendation 33; CEDAW; acces to justice; gender